Development of computational thinking tasks based on Riau Malay culture: a study of fifth-grade public school students in Pekanbaru, Indonesia - Hidayat, Riyan (Tanjung Malim, 2024)
Development of computational thinking tasks based on Riau Malay culture: a study of fifth-grade public school students in Pekanbaru, Indonesia by Hidayat, Riyan